2019
DOI: 10.3390/polym11111771
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation of Alkali Lignin with Halogen Acids and Its Application to Phenolic Resins

Abstract: Lignin, a byproduct from the chemical processing of lignocellulosic biomass, is a polyphenolic compound that has potential as a partial phenol substitute in phenolic adhesive formulations. In this study, HBr and HI were used as reagents to demethylate an alkali lignin (AL) to increase its hydroxyl content and thereby enhance its reactivity for the preparation of phenolic resins. Analyses by FT-IR, 1H-NMR and 2D-NMR(HSQC) demonstrated both a decrease in methoxyl groups and an increase in hydroxyl groups for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 30 publications
0
43
0
Order By: Relevance
“…In recent years, lignin has been used with various polymers to prepare composites and epoxy resins for different applications, i.e., surfactants, coatings, lubricants, plasticizers, carbon fiber, wastewater treatment, stabilizing agents, and fire retardant [ 1 , 8 , 45 , 46 , 47 ]. Several studies have been described the phenolization/demethylation of lignin by using various types of catalysts such as H 2 SO 4 [ 45 ], hydrogen bromide (HBr), hydrogen iodide (HI) [ 48 ], 1-dodecanethiol (DSH) [ 44 ], and Na 2 SO 3 [ 49 ] to improve the reactivity and also to reduce the molecular weight of lignin for thermoset applications ( Figure 2 a) [ 45 , 50 , 51 ]. Since HI has strong nucleophile behavior, it is a more effective catalyst for lignin demethylation than H 2 SO 4 , DSH, HBr, and Na 2 SO 3 .…”
Section: Lignin-based Resinsmentioning
confidence: 99%
“…In recent years, lignin has been used with various polymers to prepare composites and epoxy resins for different applications, i.e., surfactants, coatings, lubricants, plasticizers, carbon fiber, wastewater treatment, stabilizing agents, and fire retardant [ 1 , 8 , 45 , 46 , 47 ]. Several studies have been described the phenolization/demethylation of lignin by using various types of catalysts such as H 2 SO 4 [ 45 ], hydrogen bromide (HBr), hydrogen iodide (HI) [ 48 ], 1-dodecanethiol (DSH) [ 44 ], and Na 2 SO 3 [ 49 ] to improve the reactivity and also to reduce the molecular weight of lignin for thermoset applications ( Figure 2 a) [ 45 , 50 , 51 ]. Since HI has strong nucleophile behavior, it is a more effective catalyst for lignin demethylation than H 2 SO 4 , DSH, HBr, and Na 2 SO 3 .…”
Section: Lignin-based Resinsmentioning
confidence: 99%
“…On the other hand, demethylation (converting methoxyl to a phenolic hydroxyl group) can improve lignin reactivity toward crosslinking, degradation, and other modifications. For example, demethylated lignin had a higher reactivity in lignin-based phenolic resins, resulting in a stronger binding strength and a lower formaldehyde emission [16][17][18][19][20] . Demethylated lignin showed a higher adsorption capacity of heavy metals 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the introduction of lignin significantly enhanced the mechanical performance of polyurethane adhesives. Wang et al [12] demethylated alkali lignin with HBr and HI and then applied it in the synthesis of phenolic resin adhesives. The demethylation of lignin shortened the curing time and lowered the formaldehyde emissions of lignin-containing resins.…”
Section: Introductionmentioning
confidence: 99%